Tradition and custom at the Fiestas de San Roque, Pueblo Viejo, Chinandega (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
Reflect and describe the traditions and customs of the festivities of San Roque, from the Town of El Viejo, arises from the need to base the cultural practices that coexist in the populations of Nicaragua, specifically the study is carried out in the municipality of El Viejo, department of Chinandega. In this space thetraditional festivals that have ancestral relationship take place and for their practices they show elements of identity individually and collectively, they are accentuated in the communities and above all those that are rooted in the original culture. The main objective of this work is to present the festivities as part of the traditions and customs of the locality and how they contribute to the material and immaterial culture of the population, in this way culture, identity and cultural heritage are declared of the viejana population.
Keywords: Anthropology; Multiculturalism; Tourism; Development